THE USE OF EXTRACURRICULAR EDUCATIONAL RESOURCES IN THE DEVELOPMENT OF SPEECH SKILLS IN STUDENTS (TAMADDUN NURI JURNALI, 2025)
This article analyzes modern approaches to developing students’ speech skills, in particular, ways to increase the effectiveness of language learning through extracurricular educational resources. The author highlights the possibilities of forming students’ oral and written speech based on extracurricular materials (works of art, audio-video resources, blogs and social networks).